D5.6 Recommendations for the set-up of Open Science and Research Data Management thematic trainings - Mystakopoulos, Fotis; Sokolova, Elena; Drążewski, Kasper; Luigi Fiore, Sandro; Gotwald, Isolde; Kiesel, Megumi; Rainer, Heimo; Ritschard, Elena; Locati, Mario; Tanlongo, Federica; Avanço, Karla; Gingold, Arnaud; et al. (Zenodo (CERN European Organization for Nuclear Research), 2025)
D5.6 “Recommendations for the Set-up of Open Science and Research Data Management Thematic Trainings" outlines a strategic framework for integrating Open Science (OS) and FAIR Research Data Management (RDM) practices into research workflows. Developed under the Skills4EOSC project, the report provides recommendations for designing effective, tailored training programmes. It is intended for Competence Centres, six thematic communities and external training providers. The recommendations stem from an iterative co-creation process, including workshops, pilot training activities, and train-the-trainers sessions and aim to foster collaboration between researchers, infrastructures, and experts. The report also identifies challenges and proposes solutions for the long-term sustainability of OS/RDM training within the European research ecosystem.